Factors Related to the Use of Herbal Products and Derivatives from Consumersâ Perspective in Kota Kinabalu, Sabah: An Initial Study - Abdullah, Noraini; Salleh, Suhaimi (SOSIOHUMANIKA, 2010)
ABSTRACT: This initial study was done to identify consumersâ inclinations and perspectives on issues regarding health and natural resources in using herbs and herbal products. Questionnaires were distributed at three different locations around Kota Kinabalu, Sabah, Malaysia to respondents of different ethnic and working groups. The respondents were required to respond to questions which probed factors such as consumersâ habits and behaviours, awareness and perceptions, preferences and choices as well as influences of the mass media. The study found that factors impinging on consumersâ inclinations such as product commercialisation, preferences, media influences, and job opportunities have positive impacts. The identification and property of these factors contribute to enhancement of a model for consumers development towards healthier lifestyle through increased consumption of natural and herbal products. The future application of an enhanced model which acknowledge these contributing factors would benefit planning and implementation of consumer development strategies.Key words: natural, herbal, model, consumer development, healthy lifestyle, and healing practices.Â Â About the Authors: Noraini Abdullah is a Lecturer at the Mathematics and Finance Program in the School of Science & Technology UMS (Malaysia University of Sabah). She is contactable via noraini@ums.edu.my; and Suhaimi Sallehis a Senior Lecturer at the Communication Program of the School of Social Sciences UMS (Malaysia University of Sabah). His e-mail contact is suhaimi.binsalleh@gmail.comHow to cite this article? Abdullah, Noraini & Suhaimi Salleh. (2010). âFactors Related to the Use of Herbal Products and Derivatives from Consumersâ Perspective in Kota Kinabalu, Sabah: An Initial Studyâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.1 [Mei], pp.143-154. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (February 7, 2010); Revised (March 9, 2010); and Published (May 20, 2010). Â Â Â